Improving reading and speaking skills through project-based learning for EFL students in the form of student-made magazine - Lia Agustina (Jurnal Linguistik Terapan, 2011)
Students of the Accountancy Department of the State Polytechnic of Malang had limited knowledge of English, and it was determined much by inadequate strategy applied. Students who are studying at the second year at this department were exposed to English texts provided by the teachers, therefore, they were not prepared to read authentic texts, longer passages or let alone reading them independently. Furthermore, students also found hindrances in expressing themselves orally. They were frequently reluctant to express their ideas, even when they were asked by the teacher. These students also admitted that their main problem was their limited vocabulary skill. In this department, reading, speaking, and structure were taught separately, not integrated while vocabulary had never been given priority, as it was taught during the teaching of other skills. This article is a report of a research to see how the students‐made newsmagazine through project‐based learning can be implemented effectively to develop their English reading and speaking skills. This action research was implemented for one semester of 14 meetings. The students were assigned to have extensive reading through which they would experience authentic reading exposure and collect new words. Then, the new words should be learned and memorized by putting them in sentential contexts on their summaries and synthesis of the articles the students had chosen, read and produced the oral report of retelling activities. The students were assigned to summarize 3 authentic articles based on their interest and level of difficulty. This strategy was proved effective in improving students’ English reading and speaking skills. For further researchers, however, it is suggested that they conduct similar studies on integrated courses that emphasize on improving students English’ proficiency. They are also suggested to implement the project for two semesters.